Analisis Faktor-Faktor Equity Risk Premium Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia - Vanny Sahtria Pardede; Ali Muktiyanto; Hety Budiyanti (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to analyze the determinants of equity risk premium among healthcare sector companies listed on the Indonesia Stock Exchange during the period from 2011 to 2022. The equity risk premium, a crucial concept in investment decision-making, represents the additional return investors require for holding risky assets compared to risk-free assets. The study uses independent variables such as book to market equity ratio, beta, leverage, and firm size to understand their influence on the equity risk premium. This research adopts a quantitative approach, utilizing panel data analysis to evaluate the relationships between the variables. The sample is selected using purposive sampling, focusing on healthcare companies listed on the Indonesia Stock Exchange that have published financial statements for the years 2011 to 2022. The results of the study indicate that beta significantly affect the equity risk premium in the healthcare sector. However, book to market equity ratio, leverage, and firm size do not show a significant impact on the equity risk premium. The findings contribute to the literature by providing insights into the unique determinants of the equity risk premium in the healthcare sector, particularly in the context of the Indonesian market. These insights are valuable for investors seeking to optimize their portfolios and manage risk effectively, as well as for companies aiming to improve their financial performance and investor relations.